Сравнение установок для оцифровки русских старопечатных и рукописных книг и методы обработки изображений (Библиосфера, 2010)
Hardware and software aspects of the technology for making digital copies of the Russian early printed books and manuscripts are considered. The results of the development of the digital library «Book Monuments of Siberia» in 2009 are summarized.